M. Virasoro y S. Maresca : [interview]. - Peicovich, Esteban (Colección Los Palabristas, 2007)
Esteban Peicovich tells about the life and work of Friedrich Nietzsche. Peicovich dedicates the night to Nietzsche on the 100-year anniversary of his death. Peicovich interviews philosophers Mónica Virasoro and Silvio Maresca. Virasoro and Maresca have assembled a symposium for the following week in relation to Nietzsche's anniversary. Maresca clarifies Nietzsche's physical disappearance and work. He explains the essence of Nietzsche's message and Virasoro further explains some of his ideas. Maresca explains how Nietzsche felt about certain ideologies and their prolonging of a God whom he declared dead. Virasoro clarifies Nietzsche's philosophical intent and Maresca expands on Nietzsche's goal and approach. They each explain how he actively fought against his own ideas and why. Peicovich reads a text by Nietzsche. He is to arrange another meeting with Virasoro and Maresca soon.